PENGARUH RETURN ON ASSETS TERHADAP HARGA SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Apriantini, Nining; Rachman, Fatwa Rubiar; Terawati, Mira Teram (Jurnal Nusa Akuntansi, 2024)
Profit is the most important information to get attention, especially from investors who can show the stock price of a company. One way to measure a company's stock price is to use PBV. pbv is a ratio to assess the stock price. This study aims to determine the effect of profitability on stock prices in telecommunications subsector companies in 2020-2022 which are listed on the Indonesian Stock Exchange (IDX). The technique for determining the company that marked the sample in this study used purposive sampling using 16 companies. The method in this research is descriptive verification. The data in this study used secondary data from the IDX. The analysis used is linear regression. The results showed that profitability has an effect on stock prices by 20.6% with the level of correlation between variables in the medium category.